Analisis Faktor-Faktor Yang Mempengaruhi Lama Mencari Kerja Perempuan Lulusan S1 Prodi Ekonomi Pembangunan FEB Universitas Riau - Aulia, Rahmi; Budiartiningsih, Rahmita; Utami, Bunga Chintia (Journal Economy and Currency Study (JECS), 2024)
There are various factors that cause women to experience difficulties in getting work, even though they already have a bachelor's degree. Some of them are influenced by age, salary, work experience and GPA. Therefore, researchers conducted an analysis of the factors that influence the length of time looking for work for women graduates of the Development Economics Study Program, FEB, Riau University, which aims to determine the influence of age, wages and work experience on the length of looking for work for educated female workers who graduated from the FEB Development Economics Study Program. Riau University. The analytical model used in this research is multiple linear regression data. The sample used was 78 students from a total population of 781 female students who graduated from the S1 Development Economics Study Program, Riau University from 2013 to 2018. The results of this research show that the most influential thing is the length of time looking for work for women who graduated from the Development Economics Study Program, FEB Riau University. is choosing too many jobs with the desired wage standard. Meanwhile, the factors of age, work experience and GPA have a significant influence.